Eficiência de herbicidas no controle de plantas daninhas latifoliadas em mamona - Vitorino, H.s. [UNESP]; Martins, D. [UNESP]; Costa, S.Í.a. [UNESP]; Marques, R.p. [UNESP]; Souza, G.s.f. De [UNESP]; Campos, C.f. De [UNESP] (Instituto Biológico, 2012)
The objective of this study was to evaluate the effectiveness of different herbicides, applied in direct spray, to control dicotyledonous weeds in castor beans. The herbicides tested were saflufenacil (28, 40 and 56 g ha-1), carfentrazone-ethyl (30 g ha-1), flumioxazin (25 g ha-1), glyphosate (720 g ha-1) and glyphosate + saflufenacil (720 + 28 g ha-1) applied post-emergence on three species of weeds (Richardia brasiliensis, Sida rhombifolia and Ipomoea grandifolia), and a control without herbicide. The herbicides were sprayed when the castor bean plants showed 50 to 70 cm of height. Visual assessments of the degree of control were performed at 3, 7, 14, 21 and 28 days after treatment application. The study was installed in a randomized complete block design with three replications. The herbicide saflufenacil was effective in the control of all the weeds studied, and the herbicides carfentrazone-ethyl and flumioxazin presented only satisfactory control of weeds. The mixture tested was effective in the control of all weeds.

O objetivo do presente trabalho foi avaliar a eficiência de diferentes herbicidas, aplicados em jato dirigido, no controle de plantas daninhas dicotiledôneas na cultura da mamona. Os herbicidas testados foram: saflufenacil (28, 40 e 56 g ha-1), carfentrazone-ethyl (30 g ha-1), flumioxazin (25 g ha-1), glyphosate (720 g ha-1) e glyphosate + saflufenacil (720 + 28 g ha-1) aplicados em pós-emergência em três espécies de plantas daninhas (Richardia brasilienses, Sida rhombifolia e Ipomoea grandifolia), além de uma testemunha sem aplicação de herbicida. Os herbicidas foram pulverizados quando as plantas de mamona apresentavam 0,50 a 0,70 m de altura. As avaliações visuais de controle foram realizadas aos 3, 7, 14, 21 e 28 dias após a aplicação dos tratamentos. O estudo foi instalado no delineamento experimental em blocos casualizados, com três repetições. O herbicida saflu-fenacil foi eficiente no controle de todas as plantas daninhas estudadas, sendo que os herbicidas carfentrazone-ethyl e flumioxazin obtiveram apenas controles satisfatórios das plantas daninhas. A mistura testada foi eficiente no controle de todas as plantas daninhas.
Effectiveness of herbicides on weed control in castor beans
Keywords: Carfentrazone-ethyl; Ricinus communis; flumioxazin; saflufenacil; Carfentrazone-ethyl; Ricinus communis; flumioxazin; saflufenacil